Pseudo-Patela Baixa após Artroplastia Total do Joelho: Avaliação Radiológica e Repercussão Clínica - André Gonçalo dos Santos (2021)
Background: Anterior knee pain is an important complication after total knee arthroplasty (TKA). One of the possible contributors is the elevation of the joint line, also known as pseudo-patella baja (PPB). Limited research has been conducted regarding this condition impacting TKA management. This study aims to evaluate the incidence, identify possible related factors and assess PPB clinical repercussions. Methods: 813 consecutive TKAs between the 1st of January 2016 and the 24th of March 2019 were selected and retrospectively reviewed. Patients were submitted to the same surgical procedure using 2 different prosthesis types - Advance Wright's and Vanguard Biomet's - and information regarding implant sizes and polyethylene thickness was collected. Lateral postoperative knee radiographs at 30º flexion were analyzed to identify PPB using the modified Insall-Salvati Ratio (mISR) and the Blackburne Peel Index (BPI). An additional clinical evaluation was conducted on 112 knees via a telephone call, where the Oxford Knee and the Kujala Scores were applied, as well as an evaluation of the range of motion (ROM). Anterior knee pain was assessed using the numeric pain rating scale (NPRS) in addition to the need for analgesics. Results: A cohort of 612 knees from 573 patients were analyzed, from which 64 knees developed PPB, representing an incidence of 10.5%. Statistically significant differences were found for Advance component's sizes (femoral p=0.013 and tibial p=0.001), polyethylene thickness (p<0.001) and patients' height (p=0.022) with lower implant sizes, higher insert thicknesses and lower height showing an association with PPB. The PPB group had a significantly lower median Kujala score (59 vs. 70, p=0.011), reported a higher frequency of flexion contracture, and a significantly higher intensity of anterior knee pain (p=0.039). No significant differences were found between the two groups regarding age, gender, weight, body mass index, Vanguard implant sizes, Oxford Knee Score, extension deficit, and analgesics usage. Conclusion: Despite its incidence, PPB has a clinical relevance that should not be overlooked. Its prevention through the recreation of the natural position of the joint line and correct choice of implant sizes and polyethylene thickness is of major importance and should always be considered.